Role of a Disordered Steroid Metabolome in the Elucidation of Sterol and Steroid Biosynthesis - Shackleton, Cedric H. L. (2011)
In 1937 Butler and Marrian found large amounts of the steroid pregnanetriol in urine from a patient with the adrenogenital syndrome, a virilizing condition known to be caused by compromised adrenal secretion even in this pre-cortisol era. This introduced the concept of the study of altered excretion of metabolites as an in vivo tool for understanding sterol and steroid biosynthesis. This approach is still viable and has experienced renewed significance as the field of metabolomics. From the first cyclized sterol lanosterol to the most downstream product estradiol, there are probably greater than 30 steps. Based on a distinctive metabolome clinical disorders have now been attributed to about seven post-squalene cholesterol (C) biosynthetic steps and around 15 en-route to steroid hormones or needed for further metabolism of such hormones. Forty years ago it was widely perceived that the principal steroid biosynthetic defects were known but interest rekindled as novel metabolomes were documented. In his career this investigator has been involved in the study of many steroid disorders, the two most recent being P450 oxidoreductase deficiency and apparent cortisone reductase deficiency. These are of interest as they are due not to mutations in the primary catalytic enzymes of steroidogenesis but in ancillary enzymes needed for co-factor oxido-reduction A third focus of this researcher is Smith-Lemli-Opitz syndrome (SLOS), a cholesterol synthesis disorder caused by 7-dehydrocholesterol reductase mutations. The late George Schroepfer, in whose honor this article has been written, contributed greatly to defining the sterol metabolome of this condition. Defining the cause of clinically severe disorders can lead to improved treatment options. We are now involved in murine gene therapy studies for SLOS which, if successful could in the future offer an alternative therapy for this severe condition.